Genomic and phenotypic insight into Xanthomonas vesicatoria strains with different aggressiveness on tomato - Bianco, María Isabel; Ponso, María Agustina; Garita-Cambronero, Jerson; Conforte, Valeria Paola; Galván, Tadeo E.; Dunger, Germán; Morales, Gustavo M.; Vojnov, Adrián Alberto; Romero, Ana María; Cubero, Jaime; Yaryura, Pablo Marcelo (Frontiers in Microbiology, 2023)
Xanthomonas vesicatoria is one of the causal agents of bacterial spot, a disease that seriously affects the production of tomato (Solanum lycopersicum) and pepper (Capsicum annum) worldwide. In Argentina, bacterial spot is found in all tomato producing areas, with X. vesicatoria being one of the main species detected in the fields. Previously, we isolated three X. vesicatoria strains BNM 208, BNM 214 and BNM 216 from tomato plants with bacterial spot, and found they differed in their ability to form biofilm and in their degree of aggressiveness. Here, the likely causes of those differences were explored through genotypic and phenotypic studies. The genomes of the three strains were sequenced and assembled, and then compared with each other and also with 12 other publicly available X. vesicatoria genomes. Phenotypic characteristics (mainly linked to biofilm formation and virulence) were studied in vitro. Our results show that the differences observed earlier between BNM 208, BNM 214 and BNM 216 may be related to the structural characteristics of the xanthan gum produced by each strain, their repertoire of type III effectors (T3Es), the presence of certain genes associated with c-di-GMP metabolism and type IV pili (T4P). These findings on the pathogenicity mechanisms of X. vesicatoria could be useful for developing bacterial spot control strategies aimed at interfering with the infection processes.